Best of both worlds: How embeddedness fit in the host unit and the headquarters improve repatriate knowledge transfer - Froese, Fabian Jintae; Stoermer, Sebastian; Reiche, B Sebastian; Klar, Sebastian (Journal of International Business Studies, 2021)
Knowledge transfer within multinational enterprises is a source of competitive advantage. However, we know little about repatriates’ role in reverse knowledge transfer upon their return to headquarters (HQ). Using an organizational embeddedness perspective, we conceptualized how embeddedness fit – individuals’ perceived match between their knowledge and skills and the job requirements – during the expatriation assignment and upon repatriation predicts repatriate knowledge transfer. To test the hypotheses, we collected multi-wave survey data from 129 repatriates and their supervisors and developed a repatriate knowledge transfer scale. The results show that perceived organizational support from HQ positively influences embeddedness fit, both in the host unit during expatriation and in the HQ upon repatriation. Further, embeddedness fit in the HQ upon repatriation has a direct effect, while embeddedness fit in the host unit during expatriation has an indirect effect on repatriate knowledge transfer via increased communication frequency with the former host unit. In addition, we found that knowledge transfer is particularly pronounced for repatriates with both high levels of embeddedness fit in the HQ upon repatriation and frequent communication with colleagues in their former host unit. Our results highlight the critical importance of helping expatriates increase their perceived embeddedness fit for reverse knowledge transfer to occur.